Cost-effectiveness of telemedicine care for patients with uncontrolled type 2 diabetes mellitus during the COVID-19 pandemic in Saudi Arabia - Manal Faleh AlMutairi; Ayla M. Tourkmani; Alian A. Alrasheedy; Turki J. ALHarbi; Abdulaziz M. Bin Rsheed; Mohammed ALjehani; Yazed AlRuthia (SAGE Publishing, 2021)
Background and aim: Telemedicine could be used to provide diabetes care with positive clinical outcomes. Consequently, this study evaluated the cost-effectiveness of telemedicine for patients with uncontrolled type 2 diabetes mellitus (i.e. HbA1c >9). Patients and methods: This was a retrospective chart review of patients with uncontrolled type 2 diabetes attending an outpatient integrated care clinic. The study consisted of two arms, namely a telemedicine care model and a traditional care model with 100 patients in each. The clinical effectiveness (i.e. reduction in HbA1c) and the total cost in both arms were determined, and the incremental cost-effectiveness ratio was calculated. This study adopted propensity score matching. Results: The patients in the telemedicine care model had a mean reduction in their HbA1c level of 1.82 (95% CI = 1.56-2.09, p  < 0.001), while those in the traditional care model had a mean reduction of 1.54 (95% CI = 1.23-1.85, p  < 0.001). Consequently, the incremental effect was 0.28 (95% CI = −0.194 to 0.546). The mean total costs were SAR 4819.76 (US$1285.27) and SAR 4150.69 (US$1106.85) for patients in the telemedicine and traditional care models, respectively. Consequently, the incremental cost was SAR 669.07 (US$178.42) [95% CI = SAR 593.7 (US$158.32)-SAR 1013.64 (US$270.30)]. The ICER was estimated to be SAR 2372.52 (US$632.67) per 1% reduction in the level of HbA1c. Moreover, the telemedicine care model resulted in a higher cost and better outcome (i.e. reduction in the HbA1c level) with an 81.80% confidence level. Conclusion: Telemedicine care is cost-effective in managing type 2 patients with poorly controlled diabetes. Consequently, we believe that telemedicine care can be further expanded and incorporated into routine diabetes care.